Empowerment of Fisherwomen Lero Tatari Village, Sindue Sub-district, Donggala District, Central Sulawesi: Pemberdayaan Ibu-ibu Nelayan Desa Lero Tatari, Kecamatan Sindue, Kabupaten Donggala, Sulawesi Tengah - Salim, Firza Umar; Rahman, Abd; Mardjudo, Ahsan; Fitrianingsih, Sri Dewi (Yayasan Ahmar Cendekia Indonesia, 2025)
The purpose of community service activities is to empower fisherwomen in Lero Tatari Village through training in making fish balls, fish nuggets, and making liquid organic fertilizer from fish waste. Through community service activities, it is hoped that it can improve the skills of fisherwomen in the region. The specific target is to train 30 fisherwomen in Lero Tatari village in processing fishery products in the form of fish balls, fish nuggets, and liquid organic fertilizer from fish waste. The method developed in the implementation of this service activity is education and training in making fish balls, fish nuggets, and liquid organic fertilizer from fish waste. Education and training in making these products is expected to be a business opportunity for fisherwomen to support their household economy. In addition, this activity uses a learning by doing approach through groups that have been trained, namely learning while working / doing business. The implementation of the activity began with the socialization process of community service activities by a team of lecturers from the Faculty of Economics, Faculty of Agriculture and lecturers from Abdul Aziz Lamadjido University. This socialization aims to introduce the community to the activities that will be carried out. Furthermore, training activities were carried out on making fish meatballs, fish nuggets, and liquid organic fertilizer from fish waste with a demonstration technique, namely participants directly working on how to make these products whose raw materials are from fish.